Synthesis and Photophysical Properties of C3‐Symmetric Star‐Shaped Molecules Containing Heterocycles: A New Tactics for Multiple Fischer Indolization. Issue 1 (4th January 2018) - Kotha, Sambasivarao; Todeti, Saidulu; Das, Tarasankar; Datta, Anindya
Abstract: We report synthesis of several C3 ‐symmetric molecules containing three indole units with benzene ring as a central core. Triple Fischer indolization has been accomplished under green conditions using low melting mixture of L‐(+)‐tartaric acid (TA) and N, N ′‐dimethyl urea (DMU). In addition to Fischer indolization, another three popular reactions such as Friedel–Crafts acylation, Grignard reaction, and Suzuki–Miyaura cross‐coupling have been used as key steps to build C3 ‐symmetric star‐shaped molecules containing indole, furan, and thiophene moieties. Readily available inexpensive chemicals such as acetone, acetophenone, 4‐bromo acetophenone have been used as starting materials. Abstract : We report synthesis of several C3 ‐symmetric molecules containing three indole units with benzene ring as a central core. Triple Fischer indolization has been accomplished under green conditions using low melting mixture of L‐(+)‐tartaric acid (TA) and N, N ′‐dimethyl urea (DMU). In addition to Fischer indolization, another three popular reactions such as Friedel–Crafts acylation, Grignard reaction, and Suzuki–Miyaura cross‐coupling have been used as key steps to build C3 ‐symmetric star‐shaped molecules containing indole, furan, and thiophene moieties. Readily available inexpensive chemicals such as acetone, acetophenone, 4‐bromo acetophenone have been used as starting materials.